ANALISIS IMPLEMENTASI MANAJEMEN KURIKULUM DAN PENGAJARAN DI SD NAIKOTEN 1 KUPANG BERDASARKAN HASIL ANGKET GURU - Stevany Claritha Blegur; Hiwa Wonda; Yunita Kadja Jade (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the importance of school–community relationships in improving the quality of education at SDS Angkasa Kupang. A qualitative descriptive method was employed, using open interviews and questionnaires administered to five teachers. The findings show that the partnership between the school and the community is categorized as very strong, indicated by a positive response rate of 98.7%. The school has established various forms of collaboration, including environmental clean-up activities, religious programs, social services, open house events, and the use of social media for communication. In addition, parental involvement through regular communication and consultations contributes significantly to students’ academic development, character formation, and learning motivation. These findings indicate that strong school–community partnerships play a crucial role in supporting school programs and enhancing the effectiveness of the learning process.